2015
DOI: 10.1186/s13071-015-0723-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of moonlight and lunar periodicity on the efficacy of CDC light trap in sampling Phlebotomus (Larroussius) orientalis Parrot, 1936 and other Phlebotomus sandflies (Diptera: Psychodidae) in Ethiopia

Abstract: BackgroundPhlebotomus orientalis is the main sandfly vector of visceral leishmaniasis in the north and northwest of Ethiopia. CDC light traps and sticky traps are commonly used for monitoring sandfly populations. However, their trapping efficiency is greatly influenced by various environmental factors including moonlight and lunar periodicity. In view of that, the current study assessed the effect of moonlight and lunar periodicity on the performance of light traps in collecting P. orientalis.MethodsTrapping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
3
11
1
Order By: Relevance
“…Moonlight reduces the distance from which light traps are visible (Alexander, 2000). A previous study reported a strong negative association between moon illumination and Phlebotomus orientalis (Parrot, 1936) yields in light traps in Ethiopia (Gebresilassie et al, 2015), but this was not the case in the present study. The majority of sand flies were caught in traps placed indoors, where the effect of moonlight is likely to be smaller.…”
Section: Variablecontrasting
confidence: 88%
“…Moonlight reduces the distance from which light traps are visible (Alexander, 2000). A previous study reported a strong negative association between moon illumination and Phlebotomus orientalis (Parrot, 1936) yields in light traps in Ethiopia (Gebresilassie et al, 2015), but this was not the case in the present study. The majority of sand flies were caught in traps placed indoors, where the effect of moonlight is likely to be smaller.…”
Section: Variablecontrasting
confidence: 88%
“…In a similar vein, Dzhafarov () remarked that the effectiveness of the light trap is reliant upon the ‘degree of darkness’ that prevails. This, in essence, follows Verheijen's () dictum that it is the reduction in the ‘degree of contrast’ that helps explain why light traps give lower returns under a bright moonlit sky (Gebresilassie et al ., ). The light trap's ‘dependence’ upon total darkness to ‘photically disorient’ insects, in conjunction with the northward lengthening of the crepuscular, means that the light trap will become increasingly less effective until it is rendered worthless by the continuous twilight of Arctic nights (Southwood & Henderson, ).…”
Section: Discussionmentioning
confidence: 97%
“…This might explain the number of captured sand ies being lower than that the number captured at the entrance of the cave. Furthermore, moonlight or the lunar cycle may interfere with the light intensity of the traps which affects sand y collection [27][28][29]. Sand ies exhibit phototaxis, therefore, increased intensity of moon illumination may adversely affect light trap attraction.…”
Section: Trapmentioning
confidence: 99%